Marker assisted improvement for leaf rust and moisture deficit stress tolerance in wheat variety HD3086 - Sunilkumar, V.P.; Krishna, Hari; Devate, Narayana Bhat; Manjunath, Karthik Kumar; Chauhan, Divya; Singh, Shweta; Sinha, Nivedita; Singh, Jang Bahadur; Prakasha, T. L.; Pal, Dharam; Sivasamy, M.; Jain, Neelu; et al. (Frontiers in Plant Science, 2022)
There is a significant yield reduction in the wheat crop as a result of different biotic and abiotic stresses, changing climate, among them moisture deficit stress and leaf rust are the major ones affecting the wheat worldwide. HD3086 is a high-yielding wheat variety that has been released for commercial cultivation under timely sown irrigated conditions in the Indo-Gangetic plains of India. Variety HD3086 provides a good, stable yield, and it is the choice of millions of farmers in India. It becomes susceptible to most prevalent pathotypes 77-5 and 77-9 of Puccinia triticina (causing leaf rust) in the production environment and its potential yield cannot be realized under moisture deficit stress. The present study demonstrates the use of a marker-assisted back cross breeding approach to successful transfer of leaf rust resistance gene Lr24 and QTLs linked to moisture deficit stress tolerance in the background of HD3086. The genotype HI1500 was used as a donor parent that possesses leaf rust resistant gene Lr24, which confers resistance against the major pathotypes found in the production environment. It possesses inbuilt tolerance under abiotic stresses with superior quality traits. Foreground selection for gene Lr24 and drought tolerance QTLs linked to Canopy temperature (CT), Normal Differential Vegetation Index (NDVI) and Thousand Kernel Weight (TKW) in different generations of the backcrossing and selection. In BC2F2, foreground selection carried out to identify homozygous lines based on the linked markers and were advanced following pedigree based phenotypic selection. The selected lines were evaluated against P. triticina pathotypes 77-5 and 77-9 under controlled conditions. Recurrent parent recovery of the selected lines were ranged from 78-94%. The identified lines were evaluated for its tolerance to moisture stress under field conditions and its resistance to rust under artificial epiphytotic conditions for two years. In BC2F5 generation, eight positive lines for marker alleles were selected which showed resistance to leaf rust and recorded improvement in component traits of drought tolerance such as CT, NDVI, TKW and yield compared to the recurrent parent HD3086. The derived line named as HD3471 is nominated for national trials for testing and further release for commercial cultivation.